2021
DOI: 10.1111/ijcp.14665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylphenidate as a dopaminergic agent on myopia: Pilot study

Abstract: Myopia is the state where parallel rays from distant objects are focused in front of the retina. It is known that there has been a significant increase in the prevalence of myopia in the last decade. 1 Prevalence of myopia is expected to be around 2.5 million by 2025. 2 Melatonin secreted by daylight is responsible for the circadian rhythm. In the inner retina, melatonin regulate dopamine (DA) release. DA mediates light adaptation and circadian changes in visual sensitivity, entrains circadian rhythms of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The postulated mechanism (increased retinal dopamine release due to brighter light outdoors, with dopamine slowing the rate of axial elongation, 35 ) has been confirmed in studies of experimental myopia in animals 38–41 . There is some evidence that it also applies to humans 42 . The ability of increased time outdoors to slow the onset of myopia has been demonstrated in RCTs 18,43,44 and in system-wide implementation 45 .…”
Section: Increased Understanding Of the Risk Factors For Myopia—the K...mentioning
confidence: 91%
See 1 more Smart Citation
“…The postulated mechanism (increased retinal dopamine release due to brighter light outdoors, with dopamine slowing the rate of axial elongation, 35 ) has been confirmed in studies of experimental myopia in animals 38–41 . There is some evidence that it also applies to humans 42 . The ability of increased time outdoors to slow the onset of myopia has been demonstrated in RCTs 18,43,44 and in system-wide implementation 45 .…”
Section: Increased Understanding Of the Risk Factors For Myopia—the K...mentioning
confidence: 91%
“…[38][39][40][41] There is some evidence that it also applies to humans. 42 The ability of increased time outdoors to slow the onset of myopia has been demonstrated in RCTs 18,43,44 and in system-wide implementation. 45 Whether it also affects myopia progression is currently controversial.…”
Section: Time Outdoorsmentioning
confidence: 99%
“…Most of the evidence on a role for dopamine comes from studies on experimental myopia in animals, including non‐human primates, but, as expected, dopaminergic pathways also seem to be involved in humans. Specifically, systemic administration of the dopamine reuptake inhibitor methylphenidate has recently been reported to inhibit myopia development over 12 months in a small, placebo‐controlled study following 19 children (aged 8–18 years old) with attention deficit hyperactivity disorder 6 . If this dysregulation of the dopaminergic system is a universal requirement for excessive growth, restoring dopamine levels may form an effective clinical treatment for myopia in humans.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown, that intravitreal or topical application of levodopa, which is widely used in the treatment of neurological disorders involving dysregulation of the dopaminergic system, inhibits the development of experimental myopia in chickens (Thomson et al, 2019). In addition, it has been demonstrated that non-myopic children treated for attention deficit hyperactivity disorder (ADHD) with dopaminergic agents have slower developmental myopic refraction than untreated peers, providing a more direct suggestion that dopamine plays a role in human refractive development (Gurlevik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%